Implementing a Contextual Approach to Increase Learning Interest and Understanding of the Concept of Khiyar Jual Beli in Fiqh among Sixth-Grade Students at MIN 1 OKU Selatan - Habibi (Jurnal Aghniya, 2024)
Background: This study aims to increase learning interest and understanding of the concept of buying and selling in Fiqh among sixth-grade students at MIN 1 OKU SELATAN, Sindang Danau District, South OKU Regency, South Sumatra Province. Method: A contextual approach was chosen as the learning method to achieve this goal. This study was a classroom action research (CAR) conducted in two cycles, involving 18 students as participants. Results: The research results show that the application of a contextual approach significantly increased students' interest in learning Islamic jurisprudence (Fiqh). Furthermore, students' understanding of the concept of khiyar in buying and selling also experienced a positive increase. Students' active participation in learning and enthusiasm for the Fiqh material increased significantly during the research. Conclusion: This applied a contextual approach by presenting learning material on the concept of khiyar in buying and selling in Fiqh, linking it to real-life situations and examples from students' daily lives. Students were given the opportunity to discuss and actively participate in the learning. The results of the first cycle showed a 25% increase in student interest in learning and a 27.27% increase in understanding of the concept of buying and selling.